Criminal Policy Reform for Medical Personnel in Indonesia’s New Criminal Code: Legal Protection and Implementation Challenges - Hely Ramadhini Harahap, Hely Ramadhini Harahap; Ahmad Ma'mun Fikri, Ahmad Ma'mun Fikri (Research Horizon, 2025)
This study examines changes in criminal policy concerning medical personnel under Indonesia’s new Criminal Code Law Number 1 of 2023, focusing on legal protection and implementation challenges. The research is motivated by the rising number of medical malpractice cases in Indonesia, totalling 51 cases between 2023 and 2025, highlighting medical practitioners’ vulnerability to criminal liability. The study aims to analyze the scope of legal protection for medical professionals under the new Criminal Code and identify practical challenges in enforcing these regulations. A normative-juridical approach is applied, supported by empirical data from malpractice cases and court decisions involving medical personnel. Findings show that the new Criminal Code clarifies distinctions between medical negligence and inherent medical risk through specific provisions (Articles 344–346, 422–475), offering protection to practitioners who act in good faith and follow professional standards. Nonetheless, implementation challenges persist, including public misconceptions of medical risks, limited accountability mechanisms, and overlapping legal regulations. In conclusion, while the new Criminal Code advances the balance between patient rights and medical professional protection, effective law enforcement requires stronger integration with health regulations and professional disciplinary systems.